Dinamika Kode Etik KPK di Era Lesunya Praktik Hukum - Dyah Liesna Kusuma Wardani; Kayus Kayowuan Lewoleba (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In applying these principles, the participation and function of law enforcement is essential as a defence of justice especially in the awareness of the fundamental rights of the people in the legal context. In practice, however, the law enforcement agencies that are supposed to enforce such legal norms are often unable to avoid unethical practices. The CPC specifically investigates the elite of power involved in corruption crimes carrying out a noble mission to adapt to the realities of public life. Therefore, this study aims to further evaluate the extent to which the authority recipient can play their role by applying the principles in the Code of Ethics of the CPC profession to the legal objectives and code of ethics of a profession that is justice. The method used is qualitative research method of library research or known as library study. This research found that, from the moral code of ethics perspective, some failures in the implementation of professional standards were also seen in cases that occurred in the CPC. Therefore, the existence of a code of ethics of the legal profession in the CCP has become crucial to regulate the behaviour of law enforcement as implementation of fair law-enforcement.In applying these principles, the participation and function of law enforcement is essential as a defence of justice especially in the awareness of the fundamental rights of the people in the legal context. In practice, however, the law enforcement agencies that are supposed to enforce such legal norms are often unable to avoid unethical practices. The CPC specifically investigates the elite of power involved in corruption crimes carrying out a noble mission to adapt to the realities of public life. Therefore, this study aims to further evaluate the extent to which the authority recipient can play their role by applying the principles in the Code of Ethics of the CPC profession to the legal objectives and code of ethics of a profession that is justice. The method used is qualitative research method of library research or known as library study. This research found that, from the moral code of ethics perspective, some failures in the implementation of professional standards were also seen in cases that occurred in the CPC. Therefore, the existence of a code of ethics of the legal profession in the CCP has become crucial to regulate the behaviour of law enforcement as implementation of fair law-enforcement.